Groundswell Africa : A Deep Dive into Internal Climate Migration in Senegal - Rigaud, Kanta Kumari; de Sherbinin, Alex; Jones, Bryan; Abu-Ata, Nathalie E.; Adamo, Susana (World Bank, Washington, DC, 2021)
The World Bank’s flagship report Groundswell: Preparing for Internal Climate Migration finds that Sub-Saharan Africa is likely to witness high levels of climate-induced mobility (Rigaud et al. 2018). An expanded and deeper analysis through Groundswell Africa, focusing on West African countries, reaffirms this pattern region. The recent study projects that by 2050, without concrete climate and development action, West Africa could see as many as 32.0 million people move because of slow-onset climate impacts, such as water stress, drops in crop and ecosystem productivity, and sea level rise compounded by storm surge. These spatial population shifts will represent up to 3.5 percent of the total population of West Africa. Understanding the scale and the patterns of these climate-induced spatial population shifts is critical to inform policy dialogue, planning, and action to avert, minimize, and better manage climate-induced migration for dignified, productive, and sustainable outcomes. By 2050, internal climate migration in Senegal could reach more than 1 million. This figure represents 3.3 percent of the population, at the high end of the confidence interval under the pessimistic scenario, which combines high emissions with unequal development. In alternative scenarios, more inclusive and climate-friendly, the scale of climate migration would be reduced. The greatest gains in modulating the scale of climate migration are realized under the optimistic scenario, which combines low emissions with moderate development pathways. The number of climate migrants would drop from a mean value of 600,000 under the pessimistic and reference scenario in 2050 to 90,000 in 2050 under the optimistic scenario, which translates into a reduction of 85 percent. This major drop underscores the critical need for both inclusive development and low emissions to modulate the scale of climate migration, with the greatest gains achieved through early action.